Composition and diversity of brachyuran crabs in the mangroves of San Jose, Northern Samar - Flores, Ria Ariadne T.; Parilla, Richard B. (2022)
The composition and diversity of brachyuran crabs were studied in the mangroves of San Jose, Northern Samar was using time-based sampling in three stations. Results showed that there were five families, six genera and 11 species which was dominated by Parasesarma sp. A negative correlation was observed between the abundance of sesarmid and ocypodid species. The indices revealed a low diversity condition in the study site. The physico-chemical parameters were also measured and correlated with the abundance of crab species. Results showed significant correlations between temperature, pH and salinity, and the abundance of crab species. This indicated the varying environmental conditions that the brachyuran crab species were able to tolerate in the mangrove habitat.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.